Prevalence study of acute tonsillitis among pediatrics age groups - Hidaya Qarqani Bukhari (International Journal of Medical Reviews and Case Reports, 2019)
Tonsils and adenoids are the body’s first line of defense at the oropharyngeal pathway. They “sample” bacteria and viruses that enter the body through the mouth or nose.Tonsillitis is inflammation of tonsils, a common clinical condition often encountered in Pediatrics and E.N.T. practice. The management of this condition is often empirical with the choice of antibiotics not based on any culture reports. The increasing incidence of resistance in many organisms is due to Î²-lactamase production and resistance transfer factors that leads to unsuccessful medical therapy which results in recurrent or chronic forms of tonsillitis. The present study was conducted to identify the prevalent bacterial pathogens and their antibiotic sensitivity that would indicate the optimum line of treatment and prevent the complications of acute tonsillitis and avoids unnecessary surgical treatment. Study Design: The clinical and laboratory (culture and sensitivity) study on acute tonsillitis was carried in the family medicine, pediatric and ENT outpatient clinic of Al-Raed Health Center in Riyadh K.S.A., The laboratory studies was carried out in the Department of Microbiology. 100 cases of acute tonsillitis were selected 58 males and 42 females aged from 4-18 years at random from the patients attending the outpatient Department of family medicine, pediatrics and ENT durng a period of one year from July 2017 to August 2018; each selected case has been studied as per the standard procedures. The chosen patients were not given antibiotics for one week prior to the study.